THE ROLE OF AIDA IN AI-ASSISTED PROMOTIONAL CONTENT EFFECTIVENESS ON INSTAGRAM CUTEGRAM.ID - Tiffany Tiffany; Yuli Kartika Dewi (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI)-assisted content on promotional content effectiveness at Cutegram.id using the AIDA model (Attention, Interest, Desire, Action). The development of AI technology in digital content creation encourages online businesses to understand how effective such content is in attracting attention and driving meaningful consumer engagement. This research applies a quantitative method, with data collected through questionnaires distributed to followers of Cutegram.id. A total of 94 respondents were selected using purposive sampling. The data were analyzed using statistical tests in JASP to examine the relationship between AI-assisted content and promotional content effectiveness. The findings show that the overall model significantly predicts promotional content effectiveness. Interest, Desire, and Action have positive effects, with Action emerging as the strongest factor, while Attention does not have a significant influence. These results indicate that AI-assisted promotional content is more effective when it builds interest, strengthens desire, and encourages consumer action. This study provides practical implications for digital business owners in designing more effective AI-assisted promotional content that enhances promotional outcomes. Managerially, Cutegram.id should prioritize clear calls to action, simple purchasing processes, responsive communication, and AI-assisted optimization to increase conversions and improve overall promotional content effectiveness.